Screening and isolation of cold-adapted cellulose degrading bacterium: A candidate for straw degradation and De novo genome sequencing analysis - He, Zhigang; Ding, Baopeng; Ali, Qurban; Liu, Huiyu; Zhao, Ying; Wang, Xiujuan; Han, Yingzuo; Dong, Huan; Divvela, Praveen Kumar; Juan, Yinghua (Frontiers in Microbiology, 2023)
Degradation of crop straw in natural environment has been a bottleneck. There has been a recent increase in the exploration of cold-adapted microorganisms as they can solve the problem of corn straw degradation under low temperatures and offer new alternatives for the sustainable development of agriculture. The study was conducted in low-temperature (10°C) and high-efficiency cellulose-degrading bacteria were screened using carboxymethyl cellulose (CMC) selection medium and subjected to genome sequencing by the third-generation Pacbio Sequl and the second-generation Illumina Novaseq platform, and their cellulase activity was detected by 3,5-dinitrosalicylic acid (DNS) method. The results showed that the low-temperature (10°C) and high-efficiency cellulose-degrading bacterium Bacillus subtilis K1 was 4,060,823 bp in genome size, containing 4,213 genes, with 3,665, 3,656, 2,755, 3,240, 1,261, 3,336 and 4,003 genes annotated in the non-redundant protein sequence database (NR), Pfam, clusters of orthologous groups of proteins (COGs), Genome Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Annotation databases, respectively. In addition, a large number of lignocellulose degradation-related genes were annotated in the genome. The cellulose activity of B. subtilis K1 was higher, exhibiting the highest activity of endo-β-glucanase (24.69 U/ml), exo-β-glucanase (1.72 U/ml) and β-glucosaccharase (1.14 U/ml). It was found that through adding cold-adapted cellulose-degrading bacteriaK1 in the corn straw composting under 6°C (ambient temperature), the average temperature of straw composting was 58.7°C, and higher 86.7% as compared to control. The HA/FA was higher 94.02% than the control and the lignocellulose degradation rate was lower 18.01–41.39% than the control. The results provide a theoretical basis for clarifying the degradation potential of cold-adapted cellulose-degrading bacteria and improving the cellulose degradation efficiency.